Cycle performance investigation in compressed air energy storage in aquifers - Yang, Lichao; Li, Cai; Guo, Chaobin; Liu, Kai; He, Qingcheng (Thai Geoscience Journal, 2022)
Compressed air energy storage (CAES) is one of the promising technologies to store the renewable energies such as surplus solar and wind energy in a grid scale. Due to the widespread of aquifers in the world, the compressed air energy storage in aquifers (CAESA) has advantages compared to the conventional CAES technologies, which store the compressed air in caverns. In this study, numerical modeling by TOUGH3/EOS3 was conducted to simulate a field-scale application of a novel CAES by storing the compressed air in an aquifer. Four types of cycles, namely daily cycle, weekly cycle, monthly cycle and seasonal cycle, were designed to study their performances. The simulation results demonstrated that the air temperature in CAESA system increases as the cycle continues. The seasonal cycle can be achieved under appropriate conditions. The air recharge should be taken to continue the seasonal cycle. The simulation results can provide references for engineering application in future.